Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.465
|View full text |Cite
|
Sign up to set email alerts
|

Is the Privacy Paradox a Matter of Psychological Distance? An Exploratory Study of the Privacy Paradox from a Construal Level Theory Perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The finding corroborates prior research, which indicated that users of various digital technologies are willing to share most form of data for instant monetary gratification [54,55]. These responses are partly associated with peoples' perception of this information as something that only exists in a virtual world that is less likely to impact on their real life; this may have an influence on consumers' behaviours towards making such trade-off decisions [56]. For example, although our research participant Julie was concerned about how the fitness data might be used against her due to concerns about her health status, she was willing to make such a trade-off for instant monetary in exchange for sharing fitness information: Amongst all the participants only one participant was unwilling to share or link the devices and share personal data from the activity tracker for any benefits.…”
Section: Figure 1 Flybys Loyalty System Connects With Activity Tracksupporting
confidence: 86%
“…The finding corroborates prior research, which indicated that users of various digital technologies are willing to share most form of data for instant monetary gratification [54,55]. These responses are partly associated with peoples' perception of this information as something that only exists in a virtual world that is less likely to impact on their real life; this may have an influence on consumers' behaviours towards making such trade-off decisions [56]. For example, although our research participant Julie was concerned about how the fitness data might be used against her due to concerns about her health status, she was willing to make such a trade-off for instant monetary in exchange for sharing fitness information: Amongst all the participants only one participant was unwilling to share or link the devices and share personal data from the activity tracker for any benefits.…”
Section: Figure 1 Flybys Loyalty System Connects With Activity Tracksupporting
confidence: 86%
“…Psychological factors (e.g., bounded rationality, optimistic bias, mental resource availability, framing, context, habits, psychological distance, etc.) may also influence the choices (Cho et al, 2010 [Singapore]; Acquisti et al, 2013; Dinev et al, 2015; Quinn, 2016; Acquisti et al, 2017; Hallam and Zanella 2017 [mostly students]; Veltri & Ivchenko, 2017 [UK]; Bandara et al, 2018; Becker et al, 2019; Bandara et al, 2020 [Australia]; Ackermann et al, 2022). Another problem with privacy calculus is that both mood and emotion influence information disclosures (Li et al, 2008; Braunstein et al, 2011; Kehr et al, 2015 [US and Switzerland]; Li et al, 2017 [students]; Alashoor et al In press).…”
Section: Literature Reviewmentioning
confidence: 99%